Behavior of antibiotics during human necrotizing pancreatitis. - Bassi, C (1994)
The aim of the study was to verify whether antibiotics excreted by the normal pancreas are also excreted in human necrotizing pancreatitis, reaching the tissue sites of the infection. Twelve patients suffering from acute necrotizing pancreatitis were treated with imipenem-cilastatin (0.5 g), mezlocillin (2 g), gentamicin (0.08 g), amikacin (0.5 g), pefloxacin (0.4 g), and metronidazole (0.5 g). Serum and necrotic samples were collected simultaneously at different time intervals after parenteral drug administration by computed tomography-guided needle aspiration, intraoperatively, and from surgical drainages placed during surgery. Drug concentrations were determined by microbiological and high-performance liquid chromatography assays. All antibiotics reached the necrotic tissues, but with varying degrees of penetration, this being low for aminoglycosides (13%) and high in the case of pefloxacin (89%) and metronidazole (99%). The concentrations of pefloxacin (13.0 to 23 micrograms/g) and metronidazole (8.4 micrograms/g) in the necrotic samples were distinctly higher than the MICs for the organisms most commonly isolated in this disease; the concentrations in tissue of imipenem (3.35 micrograms/g) and mezlocillin (8.0 and 15.0 micrograms/g) did not always exceed the MICs for 90% of strains tested, whereas the aminoglycoside concentrations in necrotic tissue (0.5 microgram/g) were inadequate. Repeated administration of drugs (for 3, 7, 17, and 20 days) seems to enhance penetration of pefloxacin, imipenem, and metronidazole into necrotic pancreatic tissue. The choice of antibiotics in preventing infected necrosis during necrotizing pancreatitis should be based on their antimicrobial activity, penetration rate, persistence, and therapeutic concentrations in the necrotic pancreatic area. These requisites are provided by pefloxacin and metronidazole and to a variable extent by imipenem and mezlocillin.